Synthesis and characterization of a multi-functional on–off–on fluorescent oxidized graphitic carbon nitride nanosensor for iodide, chromium(vi), and ascorbic acid. Issue 38 (17th September 2019) - Yu, Jun-Ling; Hao, Lu-Yuan; Dong, Bin-Bin; Wang, Fei-Hong; Khan, Sayed Ali; Li, Zhan; Xu, Xin; Li, Qun-Xiang; Agathopoulos, Simeon
Abstract : The nano-CNO with enhanced fluorescence exhibited sensitive and selective recognition of iodides, chromium(vi ), which is promising for biosensing. Abstract : A novel multi-functional fluorescence nanosensor was developed by introducing carboxyl groups into graphitic carbon nitride. This oxidized graphitic carbon nitride nanoparticles (nano-CNO), which display enhanced fluorescence and water-solubility, exhibited sensitive and selective recognition of iodides and chromium(vi ), with a limit of detection (LOD) as 12.4 and 9.6 nM, respectively. In the nano-CNO system containing iodides, the reversible quenching effect, switched by an acid–base reaction, was attributed to the hydrogen bonds established between the I − ions and the carboxyl groups of the nano-CNO, in conjunction with the effect of the heavy I − ion. This "on–off–on" nanosensor for I − (created by introducing no metal ions at all) is promising for potential use in applications in the field of biosensors. The mechanism of highly sensitive probe for Cr(vi ) depends on inner filter effect (IFE) and collision quenching, which can also be turned on though the reduction of Cr(vi ) by ascorbic acid (AA). Density functional theory (DFT) calculations shed light on the mechanism of the enhanced fluorescence intensity of nano-CNO and on the mechanism for detecting iodides.